2022
DOI: 10.3389/fneur.2022.925225
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation outcomes at discharge from staged community-based brain injury rehabilitation: A retrospective cohort study (ABI-RESTaRT), Western Australia, 2011–2020

Abstract: ObjectiveTo evaluate change in functional independence, psychosocial functioning, and goal attainment at discharge from a slow-stream Staged Community-Based Brain Injury Rehabilitation (SCBIR) service in Western Australia, 2011–2020.MethodsRetrospective cohort study of n = 323 adults with acquired brain injury (ABI) enrolled in a post-acute SCBIR service compared against a control cohort of n = 312 with ABI admitted to three non-rehabilitation programs. Outcome measures were the UK Functional Independence Meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Full details of services are described elsewhere. 46 47 In brief, participants will be recruited from four different postacute services including the: (1) Transitional Rehabilitation Programme which is a slow-stream multidisciplinary Staged Community-Based Brain Injury Rehabilitation neurorehabilitation programme, 47 where individuals live onsite and complete rehabilitation over 12–24 months, (2) Transitional Accommodation Programme (TAP), which provides transitional care following discharge from hospital, (3) Capacity Building, which offers home-based supports as required, and (4) Supported Independent Living, a long-term care service for individuals with ABI who require support to carry out activities of daily living. The median time from injury to admission is 10.6 months and median length of stay is 20.5 months.…”
Section: Methods and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Full details of services are described elsewhere. 46 47 In brief, participants will be recruited from four different postacute services including the: (1) Transitional Rehabilitation Programme which is a slow-stream multidisciplinary Staged Community-Based Brain Injury Rehabilitation neurorehabilitation programme, 47 where individuals live onsite and complete rehabilitation over 12–24 months, (2) Transitional Accommodation Programme (TAP), which provides transitional care following discharge from hospital, (3) Capacity Building, which offers home-based supports as required, and (4) Supported Independent Living, a long-term care service for individuals with ABI who require support to carry out activities of daily living. The median time from injury to admission is 10.6 months and median length of stay is 20.5 months.…”
Section: Methods and Analysismentioning
confidence: 99%
“…The median time from injury to admission is 10.6 months and median length of stay is 20.5 months. 47 …”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is limited research specifically examining sex/gender differences in post-acute care service use and outcomes, defined as care accessed once medical or physiological stability has been reached following hospitalization (24). Prior studies have shown that engagement in post-acute care is associated with significant improvement in both functional independence and psychosocial outcomes in Australia (4)(5)(6) and internationally (25,26), and forms a critical component of long-term recovery after ABI (4). However, this research does not disaggregate outcomes by sex or gender, which is important to identify systematic differences to inform rehabilitation service planning and person-centred rehabilitation models (22).…”
mentioning
confidence: 99%